Nature, environment, and activism in nigerian literature - Egya, Sule E. 1976- (Routledge contemporary Africa series, 2020)
Nature, Environment, and Activism in Nigerian Literature is a critical study of environmental writing, covering a range of genres and generations of writers in Nigeria. With a sustained concentration on the Nigerian experience in postcolonial ecocriticism, the book pays attention to textual strategies as well as distinctive historicity at the heart of the ecological force in contemporary writing. Focusing on nature, the environment, and activism, the author decentres African ecocriticism, affirming the eco-social vision that differentiates environmental writing in Nigeria from those of other nations on the continent. The book demonstrates how Nigerian writers, beyond connecting themselves to the natures of their communities, respond to ecological problems through indigenous literary instrumentalism. Anchored on the analytical concepts of nature, environment, and activism, the study is definitive in foregrounding the contribution of Nigerian writing to studies in ecocriticism at continental and global levels. This book will be of interest to scholars of African and Postcolonial literature, ecocriticism, and the environmental humanities